Mechanisms of ion transport in Potamotrygon, a stenohaline freshwater elasmobranch native to the ion-poor blackwaters of the Rio Negro - Wood, Chris M.; Matsuo, Aline Y.O.; Gonzalez, Richard J.; Wilson, Rod W.; Patrick, Marjorie L.; Val, Adalberto Luis (Journal of Experimental Biology, 2002)
Stingrays of the family Potamotrygonidae are the only stenohaline freshwater elasmobranchs. Potomotrygon sp. collected from the ion-poor blackwaters ([Na+], [Cl-] and [Ca2+]=10-30μmoll-1, pH6.1) of the Rio Negro, Amazonas, Brazil, were ammoniotelic (91% ammonia-N, 9% urea-N excretion) and exhibited blood chemistry (Na+, Cl-, urea, ammonia and glucose levels and osmolality) typical of freshwater teleosts. Unidirectional Na+ and Cl- influx rates, measured with radiotracers, displayed saturation kinetics. The relationships for Cl- and Na+ had similar Km values (300-500 μmoll-1), but Jmax values for Cl- (approximately 950 μmol kg-1 h-1) were almost twice those for Na+ (approximately 500 μmol kg-1 h-1). Cl- efflux rates varied with external concentration, but Na+ efflux rates did not. There were no differences in the kinetic variables (Km, Jmax) for influx between animals acclimated to their native ion-poor blackwater or to ion-rich hard water, but efflux rates for both Na+ and Cl- were lower in the former, yielding much lower balance points (external Na+ or Cl- levels at which influx and efflux were equal). Na+, Cl- and Ca2+ uptake were all strongly inhibited by acute exposure to pH4.0, but efflux rates and Ca2+ binding to the body surface did not change. Na+ influx was inhibited by amiloride (10-4moll-1) and by two of its analogs, phenamil (4×10-5moll-1) and HMA (4×10-5moll-1), with the latter being slightly more potent, while Cl- fluxes were unaffected. Cl- fluxes were insensitive to DIDS (2×10-5moll-1 or 10-4moll-1) and SITS (10-4moll-1), but both influx and efflux rates were strongly inhibited by DPC (10-4moll-1) and thiocyanate (10-4moll-1). Ammonia excretion was unresponsive to large changes in water Na+ concentration, but was elevated by 70% during acute exposure to pH4.0 and transiently inhibited by approximately 50% by amiloride and its analogues. The strategy of adaptation to ion-poor blackwater appears similar to that of some Rio Negro teleosts (Cichlidae) in which low-affinity transport systems are relatively sensitive to inhibition by low pH but are complemented by low diffusive loss rates. Ionic transport systems in these freshwater elasmobranchs, although superficially similar to those in some freshwater teleosts, may bear more resemblance to their presumed evolutionary precursors in marine elasmobranchs.
Keywords: Ammonia; Chloride; Fresh Water; Glucose; Nitrogen; Sodium; Urea; Animals; Elasmobranchii; Homeostasis; Kinetics; Metabolism; Physiology; Transport At The Cellular Level; Ammonia; Animal; Biological Transport; Chlorides; Elasmobranchii; Fresh Water; Glucose; Homeostasis; Kinetics; Nitrogen; Sodium; Urea; Animalsia; Cichlidae; Dasyatidae; Elasmobranchii; Potamotrygon; Potamotrygonidae